HUBUNGAN PERSEPSI DAN MINAT IBU DENGAN PEMAKAIAN KONTRASEPSI IMPLAN DI WILAYAH PUSKESMAS JONGAYA MAKASSAR - Yuliani Siradjudin (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
ABSTRACT Objective: To know the relationship of perception and interest of mother with implant contraception usage in Jongaya Makassar Public Health Center Area 2016. Method: The research design used is cross sectional design using correlation method with total population of 39 respondents taken using purposive sampling technique. Population is the whole object of research (Arikunto, 2007). The population used in this research is all active KB acceptor from May - June 2016 in working area of ??Public Health Center of Jongaya Makassar. Result: The result of this study was 39 respondents who used implant contraception as much as 15 respondents (38,5%) and other family planning tool for 24 respondents (61,5%), for the perception of mothers who understood as many as 20 respondents (51.3 %) and mothers who did not understand as many as 19 respondents (48,7%) and for interest, interested mother counted 25 respondents (64,1%) and mother not interested 14 respondent (35,9%). Discussion: Contraception comes from the word counter which means to prevent or fight while the conception of a meeting between a mature egg cell with sperm cells. Conclusion: there is a relationship between perception and interest of mother with implant contraception usage at Health Center of Jongaya Makassar 2016